UNDERSTANDING THE BENEFITS OF FASTING AND THE PREVENTION OF DEGENERATIVE DISEASES WITH THE MAIN SOURCES OF MUHAMMADIYAH TARJIH AND HEALTH EXPERT OPINIONS - Dina Rahma Fadlilah; Triana Srisantyorini; Nurmalia Lusida; Ma’mun Murod Al-Barbasy; Iswan Iswan; Risky Akaputra (Indonesian Journal of Islam and Public Health, 2021)
Worship is doing something that is against the desire of his lust, to magnify His God. According to the scholars of fiqh, worship is doing something to achieve Allah's pleasure and to expect His reward in the hereafter. Fasting comes from Arabic, from which the mufrad shaama-yashuumu-shiyaaman means "to refrain from doing something", whether it is eating, talking, or traveling. Meanwhile, in terminology, it means to refrain from eating, drinking, and listening and being accompanied by the intention from thedawn of the dawn to the setting of the sun. The method in this research is to use the literature review method. So here is visible health wisdom in the fasting law. Because fasting helps all living things to adapt to very little food and makes it able to live life naturally and normally. So that fasting can prevent degenerative diseases.